Study of fuzzy based control algorithm for dynamic voltage restorer - Taghizadeh S.; Tan N.M.L.; Karimi-Ghartemani M. (John Wiley and Sons Ltd, 2023)
Algorithms; Control systems; Damage detection; Power quality; Voltage regulators; Voltage stabilizing circuits; Battery lifetime; DVR; Dynamic voltage restorer (DVR); Electrical components; EPLL; Improved control algorithms; Phase lock loop (PLL); Sensitive loads; Fuzzy logic